ALISTER McGRATH AND EDUCATION IN SCIENCE AND RELIGION - Pinsent, Andrew (Zygon, 2022)
Alister McGrath has undoubtedly made an impressive contribution to educate people in science and religion, but what are the secrets of his success? In this article, drawn from studies of his publications and a personal interview, I highlight the priority he gives to clarity, his second-personal pedagogy, his non-partisan trustworthiness, his encouragement of diversity, and his gentle, spell-breaking humor. For all his achievements in clearing intellectual space for revelation, McGrath has, however, tended to focus much more on science in relation to natural theology than revelation. Due to this focus, I tend to classify him as a John Bunyan rather than a Dante Alighieri. Hence, McGrath, who has achieved so much in educating people in science and religion, has also left plenty of opportunities for future generations to expand on his research.